Multidimensional generalizations of the ramanujan's formulas - Wang, Mingjin (Utilitas Mathematica, 2019)
In this paper, by using probability versions of the Ra-manujan's formulas, we obtain two multidimensional generalizations of Ramanujan's formulas for Beta integrals. © 2019 Utilitas Mathematica Publishing Inc.. All rights reserved.